Vector-based analysis of cortical activity associated with dumbbell exercise using functional near-infrared spectroscopy - Kato, Toshinori (Frontiers in Sports and Active Living, 2022)
The mechanism by which the brain and muscles work together has not been fully elucidated. We propose new indices and an imaging method to understand simultaneous activities of brain during a dumbbell-lifting exercise using vector-based fNIRS. An advantage of fNIRS during excercise over other modalities is the simultaneous measurement of the levels of oxyHb and deoxyHb. The vector-based approach using fNIRS is able to calculate the angle k: Arctan (deoxyHb/ oxyHb), determining the phase of the response, and the intensity of response L indicates the amplitude of a vector, reflecting the amount of change in Hb. These indices were used as indices of brain during musle activities. Seven healthy adults were participated in this study. The task was a dumbbell-lifting exercise involving flexing and extending the elbow joints of both arms. We used several different weights from 0 kg (no dumbbell), and dumbbells weighing 14.5 kg. With fNIRS measurement, the primary motor area (M1) and the plural around areas and right biceps muscle were measured at the same time. Using angle k, representing degree of cerebral oxygen exchanges, we were able to quantitatively distinguish differences in distribution of both oxygen consumption. During dumbbell exercises, oxygen exchange increased at M1, indicating a localized increase in oxygen consumption. In the area surrounding M1, cerebral oxygen exchange decreased, and the supply of oxygen increased unaccompanied by cerebral oxygen consumption. Spatial concordance between the maximum values for degree of oxygen exchange during a task and L, was less than 20%. In other words, the hypothesis that the distribution of cerebral oxygen consumption accompanying with neuroactivation does not coincide with the distribution of cerebral oxygen supply is supported in a dumbbell-lifting exercise task study. Vector-based analysis should provide new physiological indicators for simultaneous brain and muscle function.